2014
DOI: 10.1504/ijmpt.2014.059047
|View full text |Cite
|
Sign up to set email alerts
|

A validated thermo mechanical FEM model of bead-on-plate welding

Abstract: This paper is presenting accurate FEM model of bead-on-plate welds of 316L stainless steels through thermomechanical analysis. The model was composed using ANSYS Parametric Design Language (APDL) program. In thermal analysis, mixed mode of volumetric thermal load was used to represent moving heat source. Growing weld bead was accommodated in both the thermal and mechanical models using birth and death technique. Melting phenomenon was modelled by low stiffness and zero plastic strain of melting elements. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…The isotherms due to the mobile, continuous, three-dimensional thermal source show the evolution during times t2 (s) of 0, 1, 5, 35, 200, and 400 s. At time t2(s) = 5 s, the thermal source is completely inside the solid, and the temperature reaches 2450 K, in the center of the melt pool, a result very similar to other studies. At time t2(s) = 35 s, the thermal source is not completely inside the solid any longer, and there is a significant reduction in temperature, again agreeing with the results from other studies, for example (SHEN et al, 2017) and (DARMADI; KIET-TIEU;NORRISH, 2014).…”
Section: Resultssupporting
confidence: 89%
“…The isotherms due to the mobile, continuous, three-dimensional thermal source show the evolution during times t2 (s) of 0, 1, 5, 35, 200, and 400 s. At time t2(s) = 5 s, the thermal source is completely inside the solid, and the temperature reaches 2450 K, in the center of the melt pool, a result very similar to other studies. At time t2(s) = 35 s, the thermal source is not completely inside the solid any longer, and there is a significant reduction in temperature, again agreeing with the results from other studies, for example (SHEN et al, 2017) and (DARMADI; KIET-TIEU;NORRISH, 2014).…”
Section: Resultssupporting
confidence: 89%
“…Finally, for all the cases, we have noticed for the same rate loading and the same temperature as the residual stresses increase in absolute value when the crack evolves to until reaching a maximum absolute value for a length 13 mm then to become constant for crack length greater than this value. This phenomenon is also studied by finite element method prediction of residual stresses generation and temperature histories measurement [8,19]. Figure 13.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…So, Molano et al [17] have studied thermomechanical treatment effects on residual stress generation. Another, the effect of thermal properties and weld efficiency on residual stresses in welding have been studies by Armentani et al [18,19]. However, the fatigue strength improvement is due to the combined effect of residual compressive stress and the work hardening [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a study using numerical simulation and experimental validation, authors concluded that longitudinal and circumferential stresses performed on the inner and outer surfaces and the radial direction revealed a considerable increase in weld speed and power [14]. Darmadi et al utilised a mixed heat source model, which gave a well-matched temperature distribution and weld pool shape [15]. A mathematical model of a double ellipsoidal moving heat source has been used to simulate the transient thermal analysis by finite element method [16].…”
Section: Introductionmentioning
confidence: 99%